1982
DOI: 10.1172/jci110703
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding Sites for Triiodothyronine in the Plasma Membrane of Rat Thymocytes

Abstract: A B S T R A C T As a prerequisite to studies of whether the plasma membrane of the rat thymocyte contains specific, saturable binding sites for the thyroid hormone 3,5,3'-triiodothyronine (T3), a method was developed for the isolation of a plasma membrane fraction from these cells. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This effect of T3 is evident within 20 min after the addition of the hormones; it is independent of new protein synthesis, is calcium-dependent, and is mediated by an increase in cellular cyclic AMP (cAMP) concentration secondary to an increase in adenylate cyclase activity. On the basis of these and other findings, we have suggested that this action of T3 is mediated at the level of the thymocyte plasma membrane, and consonant with this is our demonstration of the presence of specific, saturable binding sites for T3 in highly purified thymocyte plasma membrane preparations (6).…”
Section: Introductionsupporting
confidence: 85%
“…This effect of T3 is evident within 20 min after the addition of the hormones; it is independent of new protein synthesis, is calcium-dependent, and is mediated by an increase in cellular cyclic AMP (cAMP) concentration secondary to an increase in adenylate cyclase activity. On the basis of these and other findings, we have suggested that this action of T3 is mediated at the level of the thymocyte plasma membrane, and consonant with this is our demonstration of the presence of specific, saturable binding sites for T3 in highly purified thymocyte plasma membrane preparations (6).…”
Section: Introductionsupporting
confidence: 85%
“…Indeed, low plasma lipid levels, tachycardia, atrial arrhythmias, heart failure, muscle weakness and wasting are commonly found in hyperthyroid animals. Plasma membrane [89], endoplasmic reticulum [90] and mitochondria [91] have been considered as potential cellular sites of action of thyroid hormone. However, it is now generally accepted that most of the actions of thyroid hormone results from influences on trascription of T3-responsive genes, which are mediated through nuclear thyroid hormone receptors [92].…”
Section: Oxidative Stress In Experimental Hyperthyroidism and Hypothymentioning
confidence: 99%
“…In-422 P. Venditti and S. Di Meo Hyperthyroidism and oxidative stress deed, low plasma lipid levels, tachycardia, atrial arrhythmias, heart failure, muscle weakness and wasting are commonly found in hyperthyroid animals. Plasma membrane [117], endoplasmic reticulum [118] and mitochondria [119] have been considered as potential cellular sites of action of thyroid hormone. However, it is now generally accepted that most of the actions of thyroid hormone results from influences on trascription of T 3 -responsive genes, which are mediated through nuclear thyroid hormone receptors [120].…”
Section: Oxidative Stress-linked Dysfunction Of Hyperthyroid Tissuesmentioning
confidence: 99%